IP spoofing defense : current issues, trend and challenges. - Lee, Soon; Othman, Mohamed; Udzir, Noor Izura (International Information Institute, 2009)
In current Internet communication world, validity of the source of IP packet is an important issue. The problems of IP spoofing alarm legitimate users of the Internet. This paper review recent progress of spoofing defenses by various researchers.Techniques and mechanisms proposed are categorized to better illustrate the deployment and functionality of the mechanism.Overall, this paper summarizes the current anti spoofing mechanism on the Internet.